(untitled) (Biological Sciences - PJSIR, 2006)
Seasonality of cyclopoids (Crustacea : Copepoda) with regards to rainfall variations was studied in Forcados river. Samples were collected by towing two plankton nets of 55 mm and 100 mm mesh sizes at 5 knots for 5 min behind an engine boat. Site meteorological observations showed low temperature range (27.5-31.5 °C), with high rainfall (25.8-602.6 mm). Eleven cyclopoid species were identified, which exhibited seasonality due to rainfall variations. High numerical abundance was observed in the rainy season months of June to September, with peak during July. From these observations it is concluded that, seasonality in the tropics is due to rainfall variations.